Continuous dependence of solutions of a class of double diffusion convection equations on Lewis coefficients - Wang, Ze (Zhejiang da xue xue bao. Journal of Zhejiang University. Sciences edition. Li xue ban, 2022)
This paper studies the structural stability for solutions of a double diffusion perturbation model in porous medium in a bounded domain. We firstly obtain some useful a priori estimates. Using these a priori estimates, we then formulate a first order differential inequality that the solution satisfies. Finally, by integrating the inequality, we get the result of continuous dependence for the solutions on the Lewis coefficient Le. This result shows that it is accurate for the double diffusion perturbation model to be used to describe the flow in porous media.